2019
DOI: 10.1002/mbo3.872
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the occurrence of sporulating and nonsporulating pathogenic bacteria in manure and in digestate of five agricultural biogas plants

Abstract: The number of agricultural biogas plants has been increasing in the past decades in some European countries. Digestates obtained after anaerobic digestion (AD) of manure are usually spread on agricultural land; however, their hygiene status regarding pathogens posing public health and/or animal health challenges has been poorly characterized up to now in France. In this study, three replicates of manure and digestate were collected from five farm biogas plants receiving animal manure in order to assess the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Although digestates from biogas plants fed with manure contain high levels of C. perfringens (ca. 10 4 CFU/g) [32][33][34][35][36][37], no information is available on the range of toxin genes and the antimicrobial profiles of this pathogenic bacterium in agricultural digestate that is intended for land application. This is the first study to assess digestate as a potential carrier of virulent and multiresistant C. perfringens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although digestates from biogas plants fed with manure contain high levels of C. perfringens (ca. 10 4 CFU/g) [32][33][34][35][36][37], no information is available on the range of toxin genes and the antimicrobial profiles of this pathogenic bacterium in agricultural digestate that is intended for land application. This is the first study to assess digestate as a potential carrier of virulent and multiresistant C. perfringens.…”
Section: Discussionmentioning
confidence: 99%
“…Soge et al [8] also reported that the tetA(P) gene was common in isolates in water and soil. Despite the ability of C. perfringens to transfer antibiotic resistance via bacterial conjugation [7] and its ability to survive under conditions found in mesophilic anaerobic digesters (MAD) [31,32], information is lacking on the antimicrobial susceptibility of resistant C. perfringens isolates in digestate intended for land application.…”
Section: Introductionmentioning
confidence: 99%
“…paratuberculosis , showed survival for up to 2 months in mesophilic ADs. To date, it is unclear to what extent the products of AD can be rendered safe and much depends on the survival structures (such as sporulation) and strategies (such as dormancy) used by different pathogens [ 115 ].…”
Section: How Long Can Mtbc Persist In the Environment?mentioning
confidence: 99%
“…The mechanisms behind these phenomena are to be discussed in Section 4. 3 TAD: Thermophilic anaerobic digestion, 4 MSW: Municipal solid waste, 5 By default, numbers provided in this column mean microbial reduction, 6 "-" means reduction in target microorganisms, 7 "+" means increase in target microorganisms. [65,66].…”
Section: Resistance To Ad Processmentioning
confidence: 99%
“…Contamination of feedstock by various pathogens, such as Salmonella spp., Listeria spp., Giardia spp., Cryptosporidium parvum, and Campylobacter spp. [2,3] and other emerging contaminants like antibiotic resistance genes (ARG) [4], could be transmitted to the environment through waste and digestate land application if they are not properly handled [5]. In 2002, the United States Environmental Protection Agency (US EPA) disclosed that the spreading of biosolids (sewage sludge) on farm lands might cause health problem to nearby local habitants [6].…”
Section: Introductionmentioning
confidence: 99%